MANIFESTATIONS OF MONOSEMY AND POLYSEMY IN DISEASE NAMES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the manifestations of monosemy and polysemy in disease names within medical terminology, as well as the linguistic and gnoseological factors underlying them. It highlights the causes and forms of polysemy within medical micro-systems. Through examples and analysis, the study reveals semantic expansion, synonymy, homonymy, and polysemy formed through terminological elements.